Zinc availability for corn, sorghum and soybean in a clayey dark-red latosol - Ritchey, Kenneth D.; Cox, Frederick R.; Galrão, Eneas Z.; Yost, Russell S. (Pesquisa Agropecuaria Brasileira, 2014)
Two field experiments were carried out on a Typic Haplusthox (clayey, kaolinitic, isohyperthermic) originally under cerrado vegetation, to evaluate the effects of zinc on maize (Zea mays L.), sorghum (Sorghum bicolor (L.) Moench), and soybean (Glycine max (L.) Merrill) yields and the effect of pH on zinc availability to maize. In the first experiment the main plots received, once only, 0, 1, 3, 9 and 27 kg/ha of zinc broadcast. The subplots were sown in the first year with three maize genotypes; in the second year, only 'Cargill 111’ maize was sown; in the third year. 'Cargill 111’ and RS 610 sorghum were sown, while in the fourth year 'Cargill 111’and ‘lAC-2’ soybean were sown. The 3 kg/ha rate was sufficient to maintain near-maximum maize yield for at least four consecutive crops. For 'Cargill 111’maize the soil critical levels were 1.4 ppm, 1.0 ppm and 0.7 ppm for the 0.1N HCl, 0.05N HCl + 0.025N H2SO4, and DTPA-TEA extractants, respectively. In the second experiment, 75, 15 and 22.5 t/ha of lime and 0.3, and 9 kg/ha of zinc were applied in a factorial design. The pH increase decreased maize yields.